Results of preoperative screening for COVID-19 correlate with the incidence of infection in the general population -a tertiary care experience. Issue 3 (27th May 2021) - Villa, Jesus; Pannu, Tejbir; McWilliams, Carla; Kizer, Chandra; Rosenthal, Raul; Higuera, Carlos; Patel, Preetesh
ABSTRACT: Objectives : Many hospitals have recently instituted policies mandating preoperative COVID-19 testing. However, it is uncertain whether institutions can dictate such policies based on infection rates found in the general population. Therefore, the main aims of the study were to determine (1) what proportion of preoperative patients tested positive, (2) what percentage was asymptomatic, and (3) whether variations throughout time in numbers of positive patients reflected changes observed in our state.Methods: All COVID-19 preoperative screening tests (nasopharyngeal-swab RT-PCR testing) performed in our hospital between 04/13/2020 and 08/27/2020 were retrospectively reviewed. The unit of analysis was number of patients who tested negative/positive. Medical records of positive patients were reviewed to determine the presence of COVID-19 symptoms. A curve was created showing our number of positive patients per week and another one presenting the number of positive patients per day in Florida, both figures were compared.Results : A total of 7, 213 patients from all specialties were preoperatively tested, out of which 85 were positive for an overall infection rate of 1.2%. In 18% (15/85) of positive patients, it was not possible to determine symptomatology. Among remaining patients, 49% (34/70) were asymptomatic while 51% (36/70) were symptomatic for COVID-19. Peak of positive cases occurred in mid-July in both curves, and the upward and downward tendencies in positive numbers mirrored each other.Conclusion : COVID-19 infection rate among our preoperative patients was very low. Nearly 50% of positive patients were asymptomatic. Our data suggest that a tertiary hospital can promulgate COVID-19 preoperative screening policies based on infection trends observed in the general population. However, in addition to the test, patients should be encouraged to self-quarantine for 14 days before surgery.